A constructive grounded theory perspective: The influence of motivation and mutualism on the portrayal of company supervisors’ role to increase both mentor and mentee’s work efficacy - Almeda, Raymond Joshua V. (Animo Repository, 2022)
The relationship between the mentor and mentee is important in a workplace as they deal with one another most of the time. This is also applicable during internship programs wherein supervisors and interns are expected to motivate each other in teaching and learning. This paper deals with understanding how motivation and mutualism affects them in increasing work efficacy. The theoretical frameworks used were Herzberg’s Two-Factor Theory of Motivation, Social Exchange Theory, and The Mentoring Exchange. Research findings showed that intrinsic motivation, career mutualism, and interpersonal mutualism were present and positively affected work efficacy. However, extrinsic motivation was not observed in the study since the internship does not offer any allowance to interns. Based on the results, the Constructive Grounded Theory (CGT) was able to determine various related themes from the variables mentioned. Intrinsic motivation was observed in both supervisors and interns through interpersonal attraction, good communication, trust, and desire to take on new challenges. On the other hand, career advancement mutualism is bounded by career advantages, mentoring, positive organizational culture, and skills development. Lastly, interpersonal mutualism’s related themes include willingness to help, setting an example, open communication, and good mentoring relationships. It was also revealed that the credibility and initiative of supervisors, good relationships, reliable mentoring, open communication, and giving recognition to interns positively influence interns. Meanwhile, a sense of fulfillment and effectively serving as a role model motivates supervisors in mentoring the interns.